Strategi Komunikasi Pemasaran Umkm Tresna Art Dalam Meningkatkan Daya Saing Produk Batik Tulis Dan Souvenir Khas Madura - Nathasya L. Sitohang; Zahrotul Rifaah; Arnella G. Br Sebayang; Rio Kurniawan (Universitas Pakuan, 2026)
MARKETING COMMUNICATION STRATEGY OF TRESNA ART MSME IN IMPROVING THE COMPETITIVENESS OF MADURESE BATIK AND SOUVENIR PRODUCTS This study aimed to analyze the marketing communication strategy implemented by Tresna Art MSME in improving the competitiveness of Madurese batik and souvenir products. The research was motivated by the increasing competition among batik and souvenir businesses in Bangkalan Regency. A descriptive qualitative method with a constructivist paradigm was employed. Data were collected through in-depth interviews, observation, and documentation. The main informant was Supik Amin as the owner of Tresna Art. The findings showed that Tresna Art implemented marketing communication strategies through social media utilization, sales promotion, direct communication with customers, participation in exhibitions, and digital marketing activities. These strategies increased customer awareness, expanded market reach, strengthened business image, and enhanced customer loyalty. Product quality, unique batik motifs, product innovation, and customer service were also identified as supporting factors in improving product competitiveness. The study concluded that marketing communication strategies played an important role in increasing the competitiveness of Madurese batik and souvenir products amid increasingly competitive business conditions.